The impact of a proposal to relax in some Albayumkanikih variables and achievement of the effectiveness of the program discus (players clubs Najaf youth athletics) - Naji, Hayder (Journal of Physical Education, 2016)
Relax and regulate breathing aims to use as a means of psychological preparation of athletes attempt to get rid of stress, anxiety and arousal facing Sporting before or during athletic competition. otkmen importance of relaxation and regulate breathing to reduce the impact of responding to the pressure of nervous and assistance to reach the optimal level of arousal and helps the players to Panevaalathm control before during Athletic competition, and that the effectiveness of the chucking require special physical abilities and capabilities of mobility for the practice as well as some physical specifications of Rami, the performance of which depends on the application of the technical aspects in an integrated manner, which depends on Elkinmetekih respects that if the layer its image ideal would have been possible to achieve better achievement. The importance of research in the stand on the effect of relaxing the program and the organization of breathing in some variables Albaao mechanical and achievement of the effectiveness throw (disk).The research problem, it turns out most of the activities of chucking handle the case of arousal emotional high for the players through the long and short-term psychological training as well as they develop recipes player physical and skill through the usual physical training in the daily training modules without the use of relaxation training and regulate breathing, which probably helps them to minimize the impact tensile psychological for the race and thus its impact on the mechanical variables and achievement..The research aims to develop and apply the proposal to relax and regulate breathing on the research sample program as well as to identify the impact of the proposed program on some Albayumkanikih variables and processing with the players effectively throw (disk) youth. The researchers assumed in light of the goals of his research:1.The proposed program a positive effect in some Albayumkanikih and achievement variables among players effectively throw (disk) youth.The research includes theoretical studies on the following terms are exercises to relax and one of the exercises necessary and important and that will help in the delivery aimed at achievement level best, which means the rest of mind and muscle relaxant and the demise of tension with the extended body or Astelqah.The researchers used the experimental approach to design (equal groups) to suit the nature of the problem to be solved, and formed the research sample of 12 players were selected purposively sample was divided into two groups (experimental and control group) and is made up of each group (6) players were finding the situation is variable not individuals sample search.The researchers conducted a pretest to the research sample for the research variables and after ending the duration of the experimental method was conducted post-test on the same sample in the same circumstances and after obtaining the results of researchers used statistical following laws (arithmetic mean, standard deviation, t for independent samples, t non-independent samples, torsion modulus) as well as the analysis and discussion of the results obtained by the researchers. astantj following.1.If you use relaxation and breathing exercises and the organization in addition to the traditional training as possible that affect the achievement of the completion of the best2.The relaxation exercises and regular breathing exercises in addition to traditional machine Bowler of the mechanical application of the conditions to be used to throw the disc better. The researchers recommend the following:1.The effectiveness of the discus coaches take advantage of the relaxation and regulate breathing exercises help being aimed at the development of better achievement.2.further research and studies to identify the nature of the study on the rest of the athletics events.